Menafsirkan Tuntutan Rakyat di Era Digital: Studi Resepsi Audiens terhadap Narasi 17+8 di Media Sosial - Siti Umaiyah (UPT Publikasi Ilmiah UNISBA, 2026)
The existence of social media has now become a new public space, where social media not only presents entertainment content but also becomes a space for quite dynamic political, social, and cultural discourse. The demands of the people of 17+8 are one form of discourse space that occurs on social media. This study seeks to understand how Generation Z as active social media users interpret and respond to the narrative of the demands of the people of 17+8 that went viral on Instagram. By using a reception study approach with a qualitative approach, this study explores the meaning that Generation Z constructs on the issue and how they produce and disseminate content related to these demands. Data were collected through in-depth interviews with 6 Generation Z who are active in the 17+8 issue. The results of the study indicate that the majority of informants are in a dominant position, where they receive the message of the People's Demands 17+8 according to the meaning expected by the creator of the narrative, namely as a form of legitimate public aspiration that needs to be fought for.